NUSANTARA CHRISTIANITY: The Synthesis Contextual Theology and Culture in Indonesia - Tandana, Ester Agustini; Tanasyah, Yusak (MAHABBAH: Journal of Religion and Education, 2023)
Like other sorts of knowledge, thought, and behavior, Christian theology is influenced by the context in which it is employed. Contextual theology shows how thoroughly contextual Christian theology is. The significance of context has never been entirely disregarded in the development of contextual theology. The emphasis on context, however, has been most prominent at times when the Christian message appeared to be the least related to the circumstances in which it was being spoken. Indonesia as the largest archipelagic country in the world with hundreds of tribes and languages has made Indonesia an interesting place to study in developing contextual theology. Based on the various languages and ethnicities that have various kinds of differences, Indonesia is unique in building a down-to-earth theology in the archipelago. This article aims to find out how contextual theology becomes a liaison in bridging between the Word and the context to be able to provide understanding for both parties to God's truth based on synthesis contextual theology and culture in Indonesia. The research method used is qualitative literature research which is the process of studying books, references, and research results to get a better understanding of a problem or issue. This information is then used to build a theoretical foundation for future research.